Feasibility study of a novel technique for treating refractory ascites using a peritoneobladder shunt in a swine model - Byeong Hwa Bak; Jung Hyuk Ko; Myoung Joo Kang; Yong June Lee; Ki Won Kim; Joo Yeon Kim; Jung Hoon Kim; Jae Joon Kim; Seok Jae Huh; Cheol Kyu Oh; Il Hwan Kim (PLoS ONE, 2025)
Ascites is often treated through paracentesis, which requires repeated application and poses risks. In this study, we developed a peritoneobladder shunt that allows natural ascites drainage from the peritoneal cavity to the bladder. We conducted an experiment to determine the functional effect of the peritoneobladder shunt in a swine model. Peritoneobladder shunts were developed and placed in 4 swine models to test their effectiveness in draining ascitic fluid from the peritoneal cavity to the bladder. The peritoneobladder shunts were inserted laparoscopically; some models received the shunts with one-way check valves to prevent fluid reflux, while one received peritoneobladder shunts without the valves. After a short (7 days) survival period, experiments were conducted to verify that the peritoneobladder shunts were properly fixed in the bladder. During the survival period, two peritoneobladder shunts could be placed in the bladder wall without rupture or tearing. When the peritoneal cavity was filled with an ascitic fluid substitute, the fluid naturally drained into the bladder; when the peritoneobladder shunts with one-way check valves were used, no reflux occurred from the bladder into the peritoneal cavity. In experiments using swine models, the peritoneobladder shunts effectively drained fluid, and one-way check valves successfully prevented reflux. These findings suggest that the peritoneobladder shunt could be an alternative option to alleviate the burden on patients who require paracentesis, allowing home-based treatment. Further studies are needed to assess the long-term stability and safety of this procedure in humans.